Panorama epidemiológico dos defeitos congênitos em Honduras - Buckley, Michelle Melissa Miralda (2021)
Introduction: Honduras is the second poorest country in Central America. The country's total population in 2019 was 9,181,487; the child population, including children under the age of five, represented about 14.8% of the total population. In 2018, the birth rate was 22 births/1,000 inhabitants, the infant mortality rate was 15.1 deaths/1,000 live births, with congenital anomalies being the second cause of infant mortality. Congenital defect comprises all structural or functional anomalies, including metabolic defects, resulting from factors originating before birth, even if the defect is not apparent or identified in the newborn, being recognized later. Birth defects are a public health problem worldwide, seriously affecting children's health and can produce disabilities. In Latin America and the Caribbean, birth defects are estimated to be responsible for about 21% of mortality among children under five years of age. Aim: This study evaluated the impact of birth defects on the morbidity and mortality of Honduran children and the development and implementation of neonatal screening in Honduras. Methodology: This is a quantitative, descriptive, retrospective, and cross-sectional study. The research was developed in two parts: (1) information on the prevalence of structural birth defects in the first year of life and in infant mortality, during the years 2014 to 2018; and (2) information about neonatal screening and functional birth defects in 2018 and 2019. Results: Over the five years studied, the prevalence of birth defects in children under 1 year of age was 256.32: 10,000. Twelve birth defects reached a frequency greater than 5: 10,000, enough to be considered non-rare. The infant mortality rate due to birth defects was 33.81: 10,000. The proportional infant mortality rate due to congenital defects was 23.83%. Concerning the neonatal screening, in 2018 and 2019, 19,911 newborns were tested for five functional birth defects: hypothyroidism, cystic fibrosis, galactosemia, phenylketonuria, and adrenal hyperplasia. Abnormalities were identified in 18 newborns, corresponding to a prevalence of 9.04:10,000. Considering all births in Honduras, the estimated coverage of screening ranged between 4.39% and 5.74%. Conclusions: Birth defects have a great impact on the morbidity and mortality of Honduran children. The surveillance system for structural birth defects in Honduras can be improved. For this, it is suggested: expansion of monitoring for all health units in the public and private systems; development of a notification method that can consider the child's place of residence and prevents repeated registration of the same child; and training of the human resources involved in the notification and care of children with birth defects. The results also reinforce the need to expand and consolidate neonatal screening in Honduras. For this, it is recommended: expansion of screening for health units in the Honduran public system, in all Departments of the country; a collection of samples in the first week of live births; conducting more studies to confirm the prevalence of galactosemia; inclusion of screening for hemoglobinopathies; organization of a national program that guarantees comprehensive treatment of patients; and organization of an accessible information system on neonatal screening.